P42 The impact of a catering initiative in determining food choices and salt intake in the public sector. (16th November 2010) - Geaney, F; Harrington, J; Perry, I J
Abstract : Background: The epidemic of obesity and diet-related chronic diseases are due to a considerable increase in energy intake from sugar, fat and salt in addition to a decreasing level of physical activity. Due to changes in modern lifestyles, individuals now depend on out-of-home eating. There is evidence that the catering sector can have a pivotal role in influencing our food choices. Objective: To examine whether a structured catering initiative could significantly determine food choice and salt intake in the public sector. Design: A cross-sectional comparison study in two hospitals, one of which had implemented a catering initiative focused on reducing sugar, salt and fat intakes. Setting: Two public sector hospitals in Cork, Ireland. Subjects/Methods: A total of 100 random participants aged 18–64 years (fifty, intervention and fifty, non-intervention) who consumed at least one main meal in the hospital staff canteen daily. Each respondent was asked to complete one anonymous 24 h dietary recall and a questionnaire. Food and nutrient analysis was conducted using WISP© (Weighed Intake Software Program; Tinuviel Software, Warrington, UK). Results: Reported mean intakes of total fat (p<0.000), saturated fat (p<0.000), salt (p<0.046) and total sugars (p<0.001) were significantly lower in the intervention hospital when adjusting for age and gender. In the intervention hospital, 43% of respondents exceeded the recommended salt intake of 4–6 g/day vs 57% of respondents in the non-intervention hospital. Significantly, 72% of respondents in the intervention hospital vs 42% in the non-intervention hospital complied with the recommended under-3 daily servings of foods high in fats and sugar (eg, oils, butter and cakes) (p<0.005). Conclusion: A hospital with a structured catering initiative can serve as a supportive environment to aid the determination of nutritious food choices and reduced salt intake. More public health efforts and health policy changes are needed to motivate caterers in the public sector and other industries into developing interventions that cater to a healthy diet.